2017
DOI: 10.1148/radiol.2016160890
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Photon-counting CT: Initial Experience with Dual–Contrast Agent K-Edge Colonography

Abstract: Purpose To investigate the feasibility of using spectral photon-counting computed tomography (CT) to differentiate between gadolinium-based and nonionic iodine-based contrast material in a colon phantom by using the characteristic k edge of gadolinium. Materials and Methods A custom-made colon phantom was filled with nonionic iodine-based contrast material, and a gadolinium-filled capsule representing a contrast material-enhanced polyp was positioned on the colon wall. The colon phantom was scanned with a prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 23 publications
0
106
0
3
Order By: Relevance
“…The 25 keV threshold was used to reject electronic noise, while the 50 and 90 keV thresholds were used to capture the K‐edge of Gd and Bi, respectively. Setting thresholds based on K‐edges helps improving the differentiation of these contrast agents, as shown in various studies …”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The 25 keV threshold was used to reject electronic noise, while the 50 and 90 keV thresholds were used to capture the K‐edge of Gd and Bi, respectively. Setting thresholds based on K‐edges helps improving the differentiation of these contrast agents, as shown in various studies …”
Section: Methodsmentioning
confidence: 93%
“…With PCD‐CT, a series of energy‐bin images can be generated from a single data acquisition, with each energy‐bin image representing the photons detected within a user‐defined energy window. This allows PCD‐CT to measure the change in x‐ray attenuation due to the K‐edges present in materials such as gadolinium (Gd) and bismuth (Bi) …”
Section: Introductionmentioning
confidence: 99%
“…Differentiation of enteric and intravascular contrast materials may be useful in trauma imaging, where identification of the source of free intra‐abdominal contrast medium enables diagnosis of hemorrhage versus bowel perforation . Muenzel et al demonstrated the potential of photon‐counting CT for differentiation of gadolinium‐enhanced polyps and iodine‐tagged fecal material in a colon phantom . Here, we demonstrated the possibility of using bismuth in vivo as an enteric contrast material to complement iodine and gadolinium intravascular contrast.…”
Section: Discussionmentioning
confidence: 63%
“…The material separation demonstrated in these studies, while appearing to be successful, was either qualitative without analysis of quantitative accuracy, or quantitative but limited to small object sizes suitable only for preclinical applications . More importantly, one of the major motivations for performing simultaneous dual‐contrast imaging is to reduce radiation dose . While it is well known that the process of material decomposition amplifies image noise and is therefore less dose efficient, the magnitude of this dose inefficiency has not been well established, particularly for the potential application of performing a single DECT scan to image two contrast agents vs performing two separate single‐energy CT (SECT) scans.…”
Section: Introductionmentioning
confidence: 99%
“…The use of two or more contrast agents has been primarily proposed and demonstrated using photon-counting-detectorbased multienergy CT (MECT) systems in multiple simulation studies, and phantom and animal experiments. [6][7][8][9][10] The use of dual-energy CT (DECT) to perform simultaneous imaging of two or more contrast agents (referred to as dual-or multicontrast imaging), however, has received less attention. With two contrast agents, a mixture of at least three materials (contrast materials and background materials) needs to be decomposed into the basis materials due to the take up of the contrast agent into biological tissues, such as blood or soft tissue.…”
Section: Introductionmentioning
confidence: 99%